Phenotypic diversity for morphological and productivity traits in chickpea core collection - Upadhyaya, Hari D.; Bramel, P.; Ortíz, R.; Singh, S. (Springer, 2002)
The chickpea (Cicer arietinum L.) core collection consists of 1956accessions, of which 1465 are desi, 433 kabuli, and 58 intermediate types. This core collection was evaluated for 7 morphological descriptors and 15agronomic characteristics to estimate phenotypic diversity. All the three groups differed significantly for flower colour, plant colour, dots on seed testa, seed testa texture, plant width, days to maturity, pods per plant,100-seed weight and plot yield. The kabuli and intermediate types were not significantly different for growth habit and seed colour, they differed,however, significantly from desi types for both traits. Desi, kabuli, and intermediate types were significantly different for plant width, days to maturity, pods per plant, 100-seed weight, and plot yield. Kabuli plants have broad plant width, matured late, have lowest average number of pods,highest 100-seed weight, and lowest plot yield. There were significant phenotypic correlations among the various characteristics. Two of these,between days to 50% flowering and flowering duration and between pod number and plant yield, explained 50% variation in the other trait in all three groups. Principal component analysis showed that days to 50%flowering, plant width, apical secondary branches, tertiary branches, dots on seed testa, 100-seed weight, flowering duration, basal secondary branches, seed colour, and seed testa texture were important traits in explaining multivariate polymorphism. Growth habit and basal primary branches did not significantly account for variation in the first five principal components of desi, kabuli, and intermediate types as well as for the entire core collection, indicating their low importance as chickpea descriptors. The average phenotypic diversity index was highest in the intermediate types(0.2653) and lowest in the kabuli types (0.1490). The Shannon-Weaver diversity index varied among traits between the three groups, and the diversity within a group depended upon the traits recorded.